9-3p=3

Simple and best practice solution for 9-3p=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3p=3 equation:


Simplifying
9 + -3p = 3

Solving
9 + -3p = 3

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -3p = 3 + -9

Combine like terms: 9 + -9 = 0
0 + -3p = 3 + -9
-3p = 3 + -9

Combine like terms: 3 + -9 = -6
-3p = -6

Divide each side by '-3'.
p = 2

Simplifying
p = 2

See similar equations:

| 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y | | 2(a-8)+7=5(a+2)-3a-29 | | 9x-45=5x+135 | | (2)(5)+4= | | -3x-9+8x=12x+9-7x | | solvea+4=10 | | 6x+11=-4-3x | | 3x-14=7x-10 | | 18=10e^4x | | z+29=47 | | -5-4a=27 | | y-10+x+5=180 | | 17+5x=-16+2x | | 2x^8-200=0 | | s+44=83 | | 5x^4+3x+(4-3x^4)*2=27 | | k+-28=-87 |

Equations solver categories